1977
DOI: 10.1002/1097-0142(197706)39:6<2923::aid-cncr2820390679>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined chemo- and hormonal therapy in advanced breast cancer

Abstract: In a randomized study sf 213 evaluable patients, a combination of hormone and polychemotherapy was compared with polychemotherapy alone. Three types of hormonal treatment were employed. The choice was dependent upon menopausal status or previous hormonal therapy. Forty-two pre-menopausal women were treated either with oophorectomy plus a modified five-drug "Cooper" combination or with the chemotherapy regimen alone. Oral methotrexate, cyclophosphamide and prednisone for two weeks was alternated with two-week c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Response rates for the treatment of bone metastases with hormonal therapy or chemotherapy generally have been lower than overall tumor response rates. Randomized studies have shown objective radiologic response rates in bone varying widely from 0–58% for either chemotherapy11, 12 or combined hormonal and chemotherapy13, 14 regimens. Bone pain may be relieved with antineoplastic treatment, usually more so with hormonal treatment than with chemotherapy.…”
mentioning
confidence: 99%
“…Response rates for the treatment of bone metastases with hormonal therapy or chemotherapy generally have been lower than overall tumor response rates. Randomized studies have shown objective radiologic response rates in bone varying widely from 0–58% for either chemotherapy11, 12 or combined hormonal and chemotherapy13, 14 regimens. Bone pain may be relieved with antineoplastic treatment, usually more so with hormonal treatment than with chemotherapy.…”
mentioning
confidence: 99%
“…Although there have been a large number of studies concluding the increased clinical response rate of tumours in the combined strategy of chemotherapy and endocrinotherapy compared to chemotherapy alone to treat advanced HRpositive breast tumours [48][49][50], there are a paucity of clinical trials comparing the clinical utility of the combination to endocrinotherapy or chemotherapy in a neoadjuvant setting. Of these, most indicate no differences of pCR rate and ORR between postmenopausal HR-positive breast cancer women who undergo NCET and monotherapy of NET or NCT, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate observed with any of the three treatment modalities is very similar to that obtained by other investigators employing Adriamycin-containing regimens . Furthermore, although patients in each of the three treatment groups received a variety of chemoinimunotherapy protocols, we have previously demonstrated that there is no significant difference in the response rate, duration of response, and survival in our patients treated with these various programs [20-231. In a randomized study conducted by the Swiss group for clinical cancer research (SAKK) for premenopausal patients treated with either chemotherapy alone or simultaneous oopliorectomy-chemotherapy [3] , and improved median duration of remission of 9.5 months was. observed for the simultaneous group as opposed to 7.8 months for those treated with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…No specific selection criteria were used as to the type of treatment given to each individual patient, and the choice depended upon the bias of staff physician to whom the patient was referred. The chemotherapy employed consisted of 5-FU 500 mg/m2 IV on days 1 and 8, Adriamycin 50 mg/m2 IV on day 1, and Cytoxan 500 mg/m2 on day 1 (FAC), and the cycle was repeated every 21 days; except for 15 patients who received ftorafur at 2 gm/m2 days [1][2][3][4][5] in place of 5-FU. The immunotherapy consisted of either BCG (6 X 10' organisms) by scarification of extremities 011 days 9 , 13, and 17 of every 21-day cycle or levamisole 100 mg/m2 orally twice weekly, or a combination of both.…”
Section: Methodsmentioning
confidence: 99%